2022
DOI: 10.1039/d1cc07249h
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochromic luminescence of a bionanocomposite hydrogel

Abstract: Bionanocomposite hydrogels were prepared from gelatin hydrogel and subsequent ionic crosslinking in the presence of the smectite with adsorbed cyanine dye (pseudoisocyanine). In addition to the improved mechanical properties achieved...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
2
10
0
Order By: Relevance
“…The PL changed from red to blue ( t = 0–6 min) upon swelling. The blue color is coming from the PIC monomer and gelatin through the aggregation-induced emission mechanism, as reported previously. , The change in the PL color between red and blue was induced by the swelling and deswelling of the gel beads, as confirmed by the absorption and PL spectra (Figure d, Movies S2 and S3). The decrease in the PL intensity due to the excimer at 580 nm was observed upon swelling in water, which was associated with an increase in the absorbance due to the monomer band in the absorption spectra (at 520 nm).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The PL changed from red to blue ( t = 0–6 min) upon swelling. The blue color is coming from the PIC monomer and gelatin through the aggregation-induced emission mechanism, as reported previously. , The change in the PL color between red and blue was induced by the swelling and deswelling of the gel beads, as confirmed by the absorption and PL spectra (Figure d, Movies S2 and S3). The decrease in the PL intensity due to the excimer at 580 nm was observed upon swelling in water, which was associated with an increase in the absorbance due to the monomer band in the absorption spectra (at 520 nm).…”
Section: Resultssupporting
confidence: 81%
“…PIC was incorporated into the system by adsorbing it onto smectite (BN) through ion exchange in the aqueous mixture prior to mixing with the aqueous gelatin solution. The concentration of PIC (1.39 × 10 –6 mol PIC per 100 mL of the mixture) was below the Cation Exchange Capacity (CEC) (82 mequiv/100 g smectite) of the smectite in order to prevent the flocculation and to obtain a homogeneous suspension . By inducing the coil-to-helix transition of gelatin chains, physically cross-linked gel beads were successfully synthesized through the dropwise addition of an aqueous mixture in ice-cooled olive oil.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] The incorporation of a mechanism that enables the evaluation and visualisation of mechanical stimuli applied to hydrogels would be useful for understanding the nanomechanics in hydrogels, leading to longer lifetimes. Over the years, several mechanochromic hydrogels have been developed using fluorescence resonance energy transfer (FRET) pairs, 4 polarity-sensing dyes such as 8-anilino-1-naphthalenesulfonic acid (ANS), 5 dyegrafted prepolymer, 6 aggregation of fluorophores, 7 or structural colour change. 8 The introduction of mechanochromic mechanophores is another promising method for studying the force applied to polymer chains in hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…[161] As a consequence of the slipping of LDH sheets, the molecular conformation of NFC anions and their intermolecular interactions with LDHs were easily tuned by applying perturbations. [162] XRD-based investigations conducted on the NFC/LDH system suggested that grinding resulted in an increase in the sample's interlayer spacing. This modification further influenced the samples' fluorescent properties.…”
Section: Fluorophores Anchored To Structurally Tunable Matricesmentioning
confidence: 99%